Conformance Testing on RRM Cell Reselection Procedure Based on TTCN-3 - Hongcheng Dong; Ning Zhang; Xiaowen Li (Dianxin kexue)
In order to verify the protocol conformance of radio resource management（RRM）cell reselection in TD-LTE system，a new testing method was designed by implementing testing and test control notation version 3 （TTCN-3）abstract test suit.Furthermore，the test suit was operated on the TTworkbench developed by German Testing Tech.The graphical presentation format（GFT）and test report to check the protocol conformance of cell reselection were generated.The scheme has been successfully applied in the project development of TTCN extended testing set instrument（RRM part）in TD-LTE system.